CHARACTERISTICS AND LIQUEFACTION OF COAL FROM WARUKIN FORMATION, TABALONG AREA, SOUTH KALIMANTAN–INDONESIA - Edy Nursanto; Arifudin Idrus; Hendra Amijaya; Subagyo Pramumijoyo (Journal of Applied Geology, 2015)
Since the coal characteristic is the main controlling factors in coal liquefaction, thus five coal seams with different coal rank from Warukin Formation in Tabalong Area, South Kalimantan have been used in this study. Three seams were low rank coal (Wara 110, Wara 120, Wara 200) while two seams were medium rank (Tutupan 210 and Paringin 712). The objectives of this study was to investigate the effect of coal rank on the rate of coal conversion factor. Coal liquefaction was conducted in an autoclave on low pressure (14.7 psi) and temperature 120°C. Experiments were designed with time intervals 30, 60 and 90 minutes, respectively. The average coal properties of seam Wara 110, Wara 120 and Wara 200 were 26.65%, 5.08%, 46.26% and 30.60% for inherent moisture, ash content, volatile matter and. fixed carbon, respectively. In contrast, coal properties for seam Tutupan 210 and Paringin 712 were 18.42%, 1.81%, 23.02% and 35.76% for inherent moisture, ash content, volatile matter and fixed carbon, respectively. The maximum yields for Wara 110, Wara 120 and Wara 200 were 48.60% (30 minutes), 51.27% (60 minutes) and 46.72% (90 minutes). In comparison, Tutupan 210 and Paringin 712 resulted maximum yields of 8.22% (30 minutes), 18.35% (60 minutes), 6.23% (90 minutes). In conclusion, low rank coal has higher yield conversion compared to medium rank coal since it has higher H/C ratio. Keywords: Coal liquefaction, low rank coal, Kalimantan.